Comparative study between polypropylene and polypropylene/poliglecaprone meshes used in the correction of abdominal wall defect in rats - Utrabo,Carlos Alberto Lima (2012)
PURPOSE: To evaluate the healing process of a defect in the ventral abdominal wall of rats, comparing the polypropylene and polypropylene/poliglecaprone meshes on the 30th and 60th postoperative day. METHODS: Thirty two Wistar rats were submitted to a ventral abdominal wall defect, with integrity of the parietal peritoneum. In the repair, were used polypropylene (group A) and polypropylene/poliglecaprone (group B) meshes. The groups were subdivided into four subgroups of eight animals euthanized on the 30th (A30 and B30) and 60th postoperative day (A60 and B60). Fragments of the abdominal wall of the animals were submitted to macroscopic, tensiometric and histological evaluations. RESULTS: The tensiometry on subgroup A30 showed a mean average break point of 0.78 MPa and in A60, 0.66 Mpa. In subgroup B30 it was 0.84 MPa and in B60, 1.27 Mpa. The score of the inflammatory process showed subacute phase on A30 and B30 sub-groups and chronic inflammatory process in subgroups A30 and 60B. CONCLUSIONS: The tensile strength was higher on the wall repaired by polypropylene/poliglecaprone mesh in the 60th post-operative day. Histology showed higher concentration of fibrosis on the surface of the polypropylene mesh with a tendency to encapsulation. In polypropylene/poliglecaprone subgroups the histology showed higher concentration of fibrosis on the surface of mesh filaments.